Implementation of a Mobile Based Mount Kerinci Climbing E-Ticket Booking System to Optimize Route Quota Management - Dilan Nanda Pratama; Arif Pramudwiatmoko (Universitas Islam Kuantan Singingi, 2024)
Mount Kerinci is one of the highest mountains in Indonesia that attracts many climbers every year. Proper management of climbing quotas is needed to maintain a balance between the number of climbers and environmental sustainability. However, the manual system currently used often causes uncertainty in quota availability, overbooking, and errors in calculation. To overcome this problem, this study develops an Android-based mobile application that uses the Rapid Application Development (RAD) method for booking climbing e-tickets. This application is designed to provide transparency and efficiency in managing climbing route quotas, allowing climbers to book tickets in real-time and helping managers manage quotas more effectively. This innovation is expected to optimize climbing quota management and improve the climber experience